Systemic neurotransmitter responses to clinically approved and experimental neuropsychiatric drugs - Hamid R. Noori (Nature Portfolio, 2018)
The precise relationship between neurobehavioural effects and neurotransmitter effects of psychiatric drugs are not always understood. Here the authors develop a database documenting the neurotransmitter response in rats to 258 different neuropsychiatric drugs, and conclude that this neurotransmitter response does not, in general, reflect the current categorisation of those drugs.